2022
DOI: 10.1002/aoc.6944
|View full text |Cite
|
Sign up to set email alerts
|

Ag(I), In (III), and Sn (II) chelates of azo mesalamine drug: Characterization, DFT studies, molecular docking and biological evaluation

Abstract: A new set of Ag(I), In (III) and Sn (II) chelates based on azo dye ligand of 5-aminosalicylic acid (H 2 L) were prepared. The structures of this novel chelates have already been confirmed by elemental analysis, thermogravimetric analysis, molar conductance, X-ray diffraction (XRD), UV-Vis, Fourier-transform infrared spectroscopy (FT-IR), and mass spectra. The lower conductivity values showed the non-electrolytic nature. The kinetic and thermodynamic parameters were determined through using Coats-Redfern model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…The electron density is polarized as seen in the three‐dimensional view of MEP. Additionally, we can get the size and geometry of the molecules 77 . MEP is computed to estimate specific structural reactive sites by the change of color that indicate the electron density along the different positions in the molecule.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The electron density is polarized as seen in the three‐dimensional view of MEP. Additionally, we can get the size and geometry of the molecules 77 . MEP is computed to estimate specific structural reactive sites by the change of color that indicate the electron density along the different positions in the molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Coats-Redfern (CR) and Horowitz-Metzger methods were used to evaluate the kinetic and thermodynamic parameters (E, A, ΔH, ΔS, and ΔG) 76,77 as seen in Figures 1 and S7a,b) and Table 5. It was observed that the investigated chelates revealed high activation energy values (ΔE*) that imply their stability.…”
Section: Compoundmentioning
confidence: 99%
See 3 more Smart Citations